Enhancing information support to health and biomedical researchers: A project to support Oxford BRC-funded researchers - Harriss, E; Mackay, D; Coxall, O; Urquhart, C; Yeoman, A (Bodleian Health Care Libraries, University of Oxford, 2020)
Staff at the Bodleian Health Care Libraries conducted a research project during 2017 to explore how embedded library services could support the workflows of the biomedical and translational research community at both the University of Oxford and the Oxford University Hospitals NHS Foundation Trust. The aim of the study was to identify the key services that should be provided to healthcare and biomedical researchers and to explore whether an embedded model, similar to that of the informationist role in the USA, would be appropriate for the Oxford context. A multi-method approach was used, triangulating a critical synthesis of the literature evidence with qualitative research (interviews and focus groups). This reports the findings about the core services that should be part of the standard library offering for this community; the library service and information needs perceived by the Oxford BRC staff; their perceptions of the services that could be provided by an informationist; the skills and knowledge required by library and information services staff to deliver these informationist activities; and recommendations from the BRC-funded staff about the most effective ways to promote these services to them.